Why do we do uTQuu^T QuuTQu instead of (uTv)2(u^T v)^2(uTv)2, because to me, it seems like performing uTQuu^T Q uuTQu takes more operations than performing (uTv)2(u^T v)^2(uTv)2?
I think we do (uTv)2(u^Tv)^2(uTv)2. The :=uTQu:= u^TQu:=uTQu is just showing the equivalence to the value we want to calculate.
Why do we do uTQu instead of (uTv)2, because to me, it seems like performing uTQu takes more operations than performing (uTv)2?
I think we do (uTv)2. The :=uTQu is just showing the equivalence to the value we want to calculate.